2019
DOI: 10.3390/agronomy9110741
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Morphological Measurement Method for a Fruit Tree Canopy Based on Kinect Sensor Self-Calibration

Abstract: Perception of the fruit tree canopy is a vital technology for the intelligent control of a modern standardized orchard. Due to the complex three-dimensional (3D) structure of the fruit tree canopy, morphological parameters extracted from two-dimensional (2D) or single-perspective 3D images are not comprehensive enough. Three-dimensional information from different perspectives must be combined in order to perceive the canopy information efficiently and accurately in complex orchard field environment. The algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…For 3D plant phenotyping, few studies investigate the impact of the recording angles on the estimation of phenotypic traits. Depending on the plant and the measured trait, single recording angles can affect phenotypic measurements [31,32]. The comparison between the field and the 360 • scans of the 48 grape bunches revealed that approximately only 30-40% of the bunch structure can be recorded (due to the recording angle and depending on size and shape of the bunch and the presence of secondary bunches).…”
Section: Introductionmentioning
confidence: 99%
“…For 3D plant phenotyping, few studies investigate the impact of the recording angles on the estimation of phenotypic traits. Depending on the plant and the measured trait, single recording angles can affect phenotypic measurements [31,32]. The comparison between the field and the 360 • scans of the 48 grape bunches revealed that approximately only 30-40% of the bunch structure can be recorded (due to the recording angle and depending on size and shape of the bunch and the presence of secondary bunches).…”
Section: Introductionmentioning
confidence: 99%
“…For C. grandis var. Longanyou, because its tree height is much lower than tree height in natural forests and the branches droop to touch the ground, the crown height of grapefruit was recorded as the distance from the highest point to the lowest point of the fruit tree point cloud according to Yang's definition [2]. Therefore, crown height was calculated using Equation ( 1):…”
Section: Calculation Of Canopy Height and Crown Width Of Fruit Treesmentioning
confidence: 99%
“…The canopy adsorbs light, interacts with the external environment, and is the main place where fruit trees perform respiration and photosynthesis. Information perception studies have shown that the crown determines the growth and development of trees, which in turn affects their yield and economic benefits [2]. Canopy characteristics have important guiding significance for research related to trees, because they can usually be used for growth assessment [3], biomass estimation [4,5], pruning effect analysis [6], yield prediction [7], health assessment early disease detection [8,9] and in the use of plant protection products such as insecticides [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some other detection methods have been proposed, and laser scanning has become a common means of evaluating these methods [ 18 , 19 , 20 ]. Compared to laser scanning, the time-of-flight (TOF) camera has the advantages of speed, simplicity and low cost and the potential for use in 3D phenotyping research [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, Microsoft Kinect is widely used as a typical TOF camera.…”
Section: Introductionmentioning
confidence: 99%